Gambaran Coping Stress Orang Tua yang Memiliki Anak Disabilitas Rungu Wicara dalam Mengahadapi Stigma Masyarakat - Rifky Ainul Yakin; Shela Christine Pello; Marleny P. Panis (Universitas Muhammadiyah Manado, 2026)
Parents who have children with hearing and speech disabilities often face social stigma from their surroundings. This stigma not only affects social relationships, but also influences the psychological condition of parents and the parenting patterns they apply. This study aims to describe the coping strategies used by parents who have children with hearing and speech disabilities in facing social stigma. This study uses a descriptive qualitative approach with semi-structured interviews. This study uses a purpose sampling technique with 6 participants in Kupang City and the data is analyzed using thematic analysis to identify patterns of experience and coping strategies used by participants. The results show that the stigma experienced by parents gives rise to negative emotions, parental concerns, and obstacles in parenting. In dealing with stigma, parents used two forms of stress coping, namely problem-focused coping and emotion-focused coping, although there were differences in coping strategies between mothers and fathers. However, overall, stress coping strategies played an important role in helping parents deal with social stigma, maintain emotional balance, and maintain their role in caring for children with hearing and speech disabilities.